2019
DOI: 10.3390/ijerph17010269
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Handgrip Strength with Adverse Cardiometabolic Health among Representative Korean Adults

Abstract: Reduced muscle mass and strength are notable features of aging. Loss of muscle mass contributes to cardiometabolic health. Although many studies have focused on skeletal muscle mass, it remains unclear whether muscle strength is beneficial for cardiometabolic health. We aimed to investigate the association between handgrip strength and the risk of adverse cardiometabolic health in middle-aged and older adults in the Korean general population. The study participants included 7602 adults from the Korea National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…A Japanese study showed that changes in HDL-cholesterol were significantly and independently associated with changes in HGS in older people [ 32 ]. These results are similar to those obtained by other authors that in previous studies have demonstrated that low HDL-cholesterol levels are common in institutionalized or community-dwelling older adults with functional impairments [ 33 , 34 , 35 ]. Therefore, reduced HDL-cholesterol levels have been proposed as a general marker of “poor well-being” and reduced physical condition [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…A Japanese study showed that changes in HDL-cholesterol were significantly and independently associated with changes in HGS in older people [ 32 ]. These results are similar to those obtained by other authors that in previous studies have demonstrated that low HDL-cholesterol levels are common in institutionalized or community-dwelling older adults with functional impairments [ 33 , 34 , 35 ]. Therefore, reduced HDL-cholesterol levels have been proposed as a general marker of “poor well-being” and reduced physical condition [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…Weaker handgrip strength is a measure of sarcopenia which reflects poor intrinsic capacity and contributes to lower functional ability of older adults 47 , 48 . In addition, a growing body of literature suggests a significant association between handgrip strength and cardiometabolic disease risk 49 which further increases the rate of cognitive decline and depending upon the environment, can negatively impact functional ability 50 . Focusing on cognitive capacity, findings from this cross-sectional study show a consistent and positive association between handgrip strength and cognition in six middle income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Low HDL cholesterol was defined as <40 mg/dL for men and <50 mg/dL for women. Finally, we also computed the total number of adverse cardiometabolic risk factors and defined ‘high risk’ as ≥3 adverse or ≥4 adverse cardiometabolic risk factors [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%